Analyze the tray Spacing Effect in Tray Aerator Reactor in Increasing Dissolved Oxygen and the Application on Groundwater - Muhammad Farhan Siddik Abdillah; Euis Nurul Hidayah; Tuhu Agung Rachmanto; Nur Laili Alfiatin Mukharomah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to analyze the effect of tray spacing on increasing dissolved oxygen and to evaluate the performance of tray aerators in reducing dissolved Fe and dissolved Mn. The study was conducted in Rungkut District, Surabaya City using tray aerators as aeration reactors. This study is divided into 2 stages: optimization and application. The optimization stage analyzes the effect of tray spacing in increasing dissolved oxygen. This stage uses variations of 30 cm, 40 cm, and 60 cm spacing. The application stage employs the optimal tray spacing to reduce Fe and Mn in well water. The results showed that a tray spacing of 30 cm can increase dissolved oxygen up to 0.6 mg/L. Tray aerators used in the application stage can reduce Fe and Mn levels in well water by 39.77% and 20.19%, respectively. The results of tray aerator aeration have not met the quality standards of the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2023, namely 0.2 mg/L and 0.1 mg/L. This shows that aeration is not enough to reduce Fe and Mn in well water, so it requires additional processes such as adsorption and filtration. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and Communities